2015
DOI: 10.1111/pbi.12398
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 improves lipid accumulation by increasing carbon metabolism in Chlorella sorokiniana

Abstract: SummarySupplying microalgae with extra CO 2 is a promising means for improving lipid production. The molecular mechanisms involved in lipid accumulation under conditions of elevated CO 2, however, remain to be fully elucidated. To understand how elevated CO 2 improves lipid production, we performed sequencing of Chlorella sorokiniana LS-2 cellular transcripts during growth and compared transcriptional dynamics of genes involved in carbon flow from CO 2 to triacylglycerol. These analyses identified the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 40 publications
4
35
1
1
Order By: Relevance
“…Both species invested in growth rather than storing lipids, which supported our hypothesis for C. ramentaceus (the non‐CCM species), but did not support the hypothesis that lipid content and fatty acid composition would change in L. australis (the CCM species). There are several possible explanations for the lack of biochemical response of L. australis : (a) Previous work, mainly on microalgae, has shown that it is the combination of excess carbon and limiting nitrogen (i.e., insufficient nitrogen for protein synthesis) that provides optimal conditions for an increase in carbon flow toward acetyl coenzyme A (acetyl Co‐A) and NADPH for FA synthesis (Sun et al, ). However, the nitrogen concentration used in this experiment was not likely to be limited, as the concentrations were that of ambient seawater and C:N ratios in the algal tissue were in the range consistent with nitrogen sufficiency (Atkinson & Smith, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species invested in growth rather than storing lipids, which supported our hypothesis for C. ramentaceus (the non‐CCM species), but did not support the hypothesis that lipid content and fatty acid composition would change in L. australis (the CCM species). There are several possible explanations for the lack of biochemical response of L. australis : (a) Previous work, mainly on microalgae, has shown that it is the combination of excess carbon and limiting nitrogen (i.e., insufficient nitrogen for protein synthesis) that provides optimal conditions for an increase in carbon flow toward acetyl coenzyme A (acetyl Co‐A) and NADPH for FA synthesis (Sun et al, ). However, the nitrogen concentration used in this experiment was not likely to be limited, as the concentrations were that of ambient seawater and C:N ratios in the algal tissue were in the range consistent with nitrogen sufficiency (Atkinson & Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such biochemical changes can be observed in the biomass very shortly after exposure (≤7 days) as an acclimation mechanism in membrane and/or storage lipids (Al‐Hasan, Hantash, & Radwan, ; Gosch, Lawton, Paul, Nys, & Magnusson, ). Elevated CO 2 concentrations have been shown to either increase or decrease the lipid production of several species of algae, especially when combined with nutrient limitation (Bermúdez et al, ; Sun, Chen, & Du, ). CO 2 enrichment could therefore not only result in increased growth rates, but also lead to changes in lipid storage.…”
Section: Introductionmentioning
confidence: 99%
“…Bile acid:Na + symporter) were induced compared to N‐replete cultures. This suggested that an enhanced CO 2 assimilation rate could increase carbon flux towards fatty acid synthesis (Sun et al ., ). Therefore, manipulating the culture C/N ratio by increasing the C source without altering N might be a promising strategy for mimicking the processes of N starvation and boosting lipid production in microalgae.…”
Section: Carbon–nitrogen Interconnectionmentioning
confidence: 97%
“…Even under non-nitrogen-limiting conditions, PDC subunits were also observed to be upregulated following transition from starch-rich heterotrophy (dark conditions) to lipid-rich photoautotrophy (light conditions) in the oleaginous C. pyrenoidosa [72]. Under elevated doses of CO 2 which improves lipid accumulation in microalgae, genes involved in carbohydrate metabolic pathways, such as the components of the PDC, were found to be upregulated in Chlorella sorokiniana , despite a downregulation of most FA synthesis genes [102]. This implies that the positive correlation between PDC expression and lipid buildup is not primarily confined to nutrient-depleted conditions.…”
Section: Introductionmentioning
confidence: 99%